IMPLEMENTATION OF ONLINE DISPUTE RESOLUTION (ODR) AS AN ALTERNATIVE DISPUTE RESOLUTION IN TOKOPEDIA - Shella Oktaviani (JURNAL HUKUM DE'RECHTSSTAAT, 2022)
Settlement out of court by means of consultation, negotiation, mediation, conciliation, or expert judgment, along with the development of the times and technology that is rapidly emerging, online dispute resolution (ODR) is an alternative to online dispute resolution. This study aims to determine the concept of "online dispute resolution" (ODR) as an alternative dispute resolution and how it is applied in Tokopedia. The research method used in this study is a normative legal research method, using two types of data, namely primary data and secondary data. Data collection techniques and literature study.The result of this research is online dispute resolution (ODR) as an alternative dispute resolution using information communication technology in practice. It is carried out efficiently, quickly and easily. in dispute resolution. There is a need for specific laws and regulations governing the practice of online dispute resolution (ODR) in Indonesia in order to have legal certainty, and Tokopedia is expected to further improve online dispute resolution (ODR) services.